PENDAMPINGAN HUKUM BAGI MASYARAKAT MARGINAL DI KOTA BAUBAU DALAM MEMAHAMI HAK-HAK DASAR KEWARGANEGARAAN - Abdullah, La Ode Dedi; Tri Pratiwi, Endang; Abdullah, Rudi; Agustina, Wa Ode (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Marginalized communities in Baubau City frequently face barriers in accessing legal information, particularly regarding fundamental citizenship rights such as education, healthcare, legal protection, and participation in development. The lack of awareness of these rights may lead to violations or social injustice. This community service program aims to provide participatory legal assistance through counseling, individual consultations, and complaint procedure simulations. The activities involve collaboration with local legal aid institutions, traditional leaders, and local government to ensure an inclusive approach. Expected outcomes include increased legal awareness among the community, simplified educational modules, and the establishment of a sustainable assistance network. This initiative not only promotes the fulfillment of constitutional rights but also strengthens community capacity to address legal disparities.